Theoretical and Methodological Principles of Teaching Professional English to Future Doctors - Rusalkina, Liudmyla; Tomashevska , Agnessa (East European Journal of Psycholinguistics, 2022)
Modern social processes determine new vital areas of reconstruction of the educational process in higher medical school on the way to teaching future professionals in all fields of medicine. The objective reality of Ukraine’s development today is the expansion of international ties and integration into the European community. Medical professionals’ knowledge of foreign languages ​​is becoming essential in such circumstances. The article aims to develop and scientifically substantiate methodological concepts and theoretical bases of the English language professional teaching of future doctors in higher medical schools, characterize the levels of English professional knowledge of medical students, analyze the findings and imply them to future research and practice. The pedagogical conditions of English-language professional teaching of future doctors such as motivational stability and awareness of the need to learn English for further professional communication; integration of professional and linguistic (English-speaking) disciplines in the educational process of the higher medical school; creation of the developmental English-speaking professional environment in medical higher schools; involvement of future doctors in active English-speaking professionally-oriented activities were defined and substantiated. The authors designed and verified the model of English-language professional teaching to future doctors in higher medical schools. Besides, they experimentally established and statistically confirmed the positive dynamics of the levels of English-language professional teaching to students in the experimental group. This was achieved due to the introduction of the designed methodology to future doctors who study at higher medical schools. The application of the Kolmogorov-Smirnov λ-test confirms the validity of the proposed model and experimental technique.